(untitled) (Teología, 2021)
Jorge Novak (1928-2001), the first Bishop of Quilmes, pointed out a path for the Church in Argentina. In his reflection we identify valid theological developments and pastoral proposals to characterize a Church «serving everyone» driven by the renewal proposed by the Second Vatican Council. In her thought and in her pastoral actions we will highlight ecclesiological reflection on an essential theme for the existence of an evangelizing Church: the development of mainly lay ministries and Services within the Christian community.